A closer look : deceptions and discoveries - Wieseman, Marjorie E.; National Gallery (Great Britain) (London : National Gallery Co., 2010)
How do experts spot masterpieces? Paintings are not always signed or documented, so how can one tell an obscure gem from an altered image? Scientists, conservators and art historians use a range of methods to examine the physical nature of pictures and unravel their hidden histories. Through a series of examples and clearly explained processes, this brand new guide will draw the reader into the complex issues confronted by gallery professionals.
boek